(untitled) (Review Journal of Neurological & Medical Sciences Review, 2023)
Sleep disorders have long been recognized as influential factors in neurological health, and recent research has shed light on the bidirectional relationship between them. This paper synthesizes current literature to elucidate the intricate interplay between sleep disturbances and neurological disorders, highlighting the mechanisms underlying their association and the clinical implications. Understanding this bidirectional relationship is crucial for developing effective interventions to improve both sleep quality and neurological outcomes. Keywords: Sleep disorders, Neurological health, Bidirectional relationship, Mechanisms, Clinical implications.